Multivariate pattern of quantitative trait variation in triploid banana and plantain cultivars - Osuji, J.O.; Okoli, B.E.; Vuylsteke, D.R.; Ortíz, R. (Elsevier, 1997)
Plantains and bananas (Musa spp. L.) are inter- or intraspecific triploid hybrids derived from crosses between M. acuminata Colla. (A genome) and M. balbisiana Colla. (B genome). Cultivars have been assigned to different taxonomic groups (AA, BB, AAA, AAB, ABB, etc.) based on morphological qualitative descriptors. Principal component analysis of 15 quantitative traits was carried out to establish a more objective taxonomic relationship of cultivar groups and subgroups in the Musa germplasm. Fruit traits, number of neutral flowers, total number of leaves, plant girth at 50 cm, and days to flowering and harvest were the major discriminating traits in the germplasm. Principal components analyses grouped Musa germplasm into AAB plantains, AAA dessert bananas and ABB cooking bananas. The AAB starchy bananas appear to be separated into two subgroups with one being close to the AAB plantains and the other being close to the ABB cooking bananas. The dwarf French AAB plantain cultivar ‘Njock Kon' appears to be a mutant of a giant AAB plantain cultivar.